Evaluasi Implementasi Pelayanan Jaminan Kesehatan Nasional pada Balai Kesehatan Paru Masyarakat (BKPM) Wilayah Semarang Terikat Kerjasama Dengan Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan - Agus Budiono; Sutopo Patria Jati; Chriswardani Suryawati (Jurnal Manajemen Kesehatan Indonesia, 2016)
Provision of National Health Insurance (JKN) on Lung Health Center Society (BKPM) Region Semarang has not been implemented optimally. Increased patient visits JKN participants in 2014 only 1% compared to the era of Askes, the discrepancy rates with real cost incurred, inadequate infrastructure services, long waiting time queuing services and the lack of agreement among stakeholders define the classification status of BKPM. The aim of research to evaluate the implementation of national health insurance on Lung Health Center Society (BKPM) Region Semarang. The research was conducted by using a qualitative in-depth interviews and review of documentation to explore the phenomenon being evaluated. This study key informants from BKPM Territory Semarang is Semarang Regional Head of BKPM, Treasurer, 1 Medical Record officers, 2 doctors clinic, and 1 administrative manager of the Health Insurance. 1 person sexy informant triangulation financing and Public Health Insurance Central Java Provincial Health Office, 1 Main Branch Health BPJS staff Semarang. Quantitative data to support the triangulation of data with customer satisfaction survey using quota sampling technique to sample 45 participants JKN patients who seek treatment in Semarang Regional BKPM. Qualitative data analysis techniques and quantitative content analysis method with frequency table. The results showed that: 1) The number of patients more than Non PBI PBI, 2) Services BKPM Semarang according to the contents successor agreement Regional cooperation but still need to be developed and improved again. 79.03% patient satisfaction that includes a satisfactory category. 3) On the financing aspects still exist discrepancies BPJS service rates with real cost Semarang Regional BKPM expenses, 4) Coordination is not maximized at the management and executive levels in Semarang Regional BKPM in the implementation of Health Insurance in early 2014. Recommendations that can be given is necessary socialization and revamping procedures JKN referral, assessment manufacture unit cost as the basis tariff scheme, infrastructure development and improvement of health services in the implementation of labor discipline JKN in Semarang Regional BKPM.